Representation of Women in the Novel "Ronggeng Dukuh Paruk" by Ahmad Tohari - Juhanah, Ai; Abdul Hasim; Deasy Aditya Damayanti; Winka Naida (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research is motivated by the phenomenon that ronggeng is a cultural heritage in the life of the Javanese people. This study used descriptive qualitative method. This study uses a qualitative approach with a direct analysis design on the novel. This is done to study the aspects of women's representation in the novel which is used as the object of study. This research shows that the novel Ronggeng Dukuh Paruk displays several discourses on sexuality. The depictions of sexual relations between Srintil and several male characters, namely Rasus, Ki Secamenggala, Dower, and Sulam show that Srintil is an object that is forced to surrender to circumstances. Srintil and Rasus have a complex relationship with the image of Mother in Srintil. Then, Srintil's relationship with Ki Secamengala was seen as a religious ritual that was sacred to the people of Dukuh Paruk. Furthermore, the relationship between Srintil, Dower and Sulam is like a buying and selling transaction. The depiction of the myths and stereotypes of the Dukuh Paruk community appears with several discourses of sexuality. This novel is also closely related to cultural values because in this novel the story is related to beliefs related to the existence of ronggeng in the hamlet. The characters in the novel highly uphold the cultural values taught by their ancestors. In addition, there are many spells such as love spells and love breaker spells as part of the representation of cultural elements in aspects of oral literature.